Maraichage urbain et semi-urbain de Moringa oleifera Lam. par des associations de femmes au Burkina Faso : contraintes et opportunités - Madjelia Cangré Ebou Dao; Josias Sanou; Souleymane Pare (VertigO)
A survey was conducted in 2014 to describe the constraints and opportunities of Moringa oleifera in the urban and suburban market gardening systems of Burkina Faso. A total of 59 women producing M. oleifera in vegetable gardening were identified in women associations of Ouagadougou (Nabonswende), Loumbila (Pan-Nafa), and Komsilga (Zemstaaba association). The results showed that 58 % of women produced M. oleifera in association with lettuce plants and 42 % in monoculture in urban and sub urban areas. The opportunities to grow this plant by women's associations are primarily to have fresh nutrient-rich leaves during the dry season when they are rare, to have cash income during dry seasons, to be key actresses of Moringa sector in Burkina Faso through the organization of a seed distribution system between private producers. The problems they face are related to the non-mastery of cultivation practices by more than 80 %, the non-access to factors of production, and the products marketing are still rudimentary. To this end, the strengthening of producing technical building and technical support systems for collecting and distribution of viable seed quality for themselves could constitute a great economic and strategic value for small producers in urban and semi urban areas of Burkina Faso. The study gave an overview of this new vegetable speculation among illiterate women without fixed income in Burkina Faso's central region. It is a starting point for further monitoring of this income generating activity for women.